Digital Comic Media Contains Contextual Material on Economic Activities Science Content for Grade V Students - I Made Yogi Setiawan; I Gusti Agung Ayu Wulandari; Maria Goreti Rini Kristiantari (Universitas Pendidikan Ganesha, 2025)
The problem that occurs in class V is the low learning outcomes of science and natural sciences. This is due to the lack of variation in learning media and the dominant lecture method. This study aims to analyze the effectiveness of Digital Comics Containing Contextual Material on the Economic Activities Material of Science Content for Class V Students. The research model used is ADDIE (analyze, design, development, implementation, evaluation). The subjects of the effectiveness test in this study were 26 students in class V. Data acquisition is classified into two types, namely quantitative and qualitative data. The research methods are observation, interviews, questionnaires and multiple-choice tests. While the instruments used are questionnaires and multiple-choice tests. The results of individual and small group test data were collected through pre-tests and post-tests. Then a prerequisite test (normality) was carried out before the hypothesis test (dependent sample t-test) was carried out. The results of the study showed that the tcount value = 17.34 was greater than ttable = 2.001. This means that tcount > ttable, so H0 is rejected and H1 is accepted. So, it can be concluded that contextual-based digital comic media is an effective content of science subjects for economic activities for grade V students.